A Study on Affiliate Marketing in Guwahati City amongst the Millennials - Juma, Dennis; Hategekimana, Jean Baptiste (Journal of Global Economy, Business and Finance, 2025)
This research study investigates the Affiliate Marketing in Guwahati City, with a specific focus on the millennials demographic. The objective of this research is gain comprehensive insights into millennials’ engagement with affiliate marketing programs, their perceptions of this marketing strategy, and the factors influencing their decision making process. To achieve the research goals, a mixed - method approach was employed, comprising both qualitative and quantitative data collection methods. In - depth interviews and surveys were conducted among 100 representative sample of millennials residing in Guwahati City to understand their experiences and opinions regarding affiliate marketing. The findings shed light on the attitudes and behaviors of millennials towards affiliate marketing in Guwahati City. Understanding these insights is essential for businesses and marketers seeking to optimize their affiliate marketing strategies and effectively target the millennial market in the region. The research also provides valuable implications for fostering trust and authenticity in affiliate marketing campaigns, which can lead to stronger brand - consumer relationships and enhanced customer loyalty among millennials.